The Effect of a Training Program Based on Marzano’s Six Step Vocabulary Process on Female EFL Teachers’ Performance in Teaching Vocabulary in the First Zarqa Directorate of Education - Al-Husban, Naima; Alkhawaldeh, Ahmad (DIRASAT: EDUCATIONAL SCIENCES, 2021)
This study aimed to examine the effect of a training program based on Marzano’s six step vocabulary process on EFL female teachers’ performance in teaching vocabulary. The sample of the study was consisted of 56 teachers who were purposefully chosen from the schools of the 1st directorate of education in Zarqa’. They were randomly divided into experimental and control groups. Teaching performance scale on vocabulary instruments was used. Analysis of covariance test (ANCOVA) was used to identify any differences between the two groups. The results revealed that the teaching performance in vocabulary of female EFL teachers in the experimental group surpassed that of EFL teachers in the control group. On the basis of the results of the study, the researcher recommended that future research be investigated on the effect of Marzano’s vocabulary process on teacher effectiveness.